Avaliação dos efeitos da fotobiomodulação na movimentação ortodôntica de verticalização de molares com mini-implantes: ensaio clínico controlado randomizado e duplo-cego - Silva, Felipe Murakami Malaquias da (2022)
The tooth loss can lead to adjacent and antagonist movement of teeth, which makes prosthetic rehabilitation difficult. Anchorage systems, such as mini screw (MS), have been increasingly used as a treatment option. Recent studies, have shown that photobiomodulation (PBM) can accelerate orthodontic movement, modulate inflammation, and decrease pain in intrusion movement. The aim of this study was to evaluate the effects of PBM on the orthodontic movement of molar verticalization, evaluating the speed of movement, the expression of the pro-inflammatory cytokine IL-1β, analgesia, and the impact of oral health treatment on quality of life. After calibration of involved researchers, thirty-four healthy individuals aged 23-72 years, in need of recovery of the prosthetic space for oral rehabilitation after loss of the 1st lower molars and mesial movement of 2nd molars, were randomly divided into 2 groups: Group A (experimental group) - verticalization through MS+ PBM; Group B (control group) – verticalization through MS + PBM simulation. The movements occur with orthodontic MSs and elastomeric chain ligatures changed every 30 days for 3 months. PBM occurred with the application of a diode laser, 808 nm, 100mW, receiving 1J per point, for 10s, in 10 points (5 buccal and 5 lingual) and radiant exposure of 25 J/cm². Applications were performed immediately, 24h, 72h, 1 and 2 months after activation, always after applying a new force. An initial and final panoramic radiograph was performed to determine the amount (in degrees) of verticalization in this time interval (90 days), which was our primary outcome. To assess pain, the Visual Analogue Scale (VAS) was used in all consultations, and to assess the impact of oral health on the participant's quality of life, the OHIP-14 questionnaire was applied. Each participant received a pattern analgesic pack, and the amount of medication was also computed. Crevicular gingival fluid (CGF) was collected at baseline, 24h and 72h of the first month only. The cytokine IL-1β was analyzed by ELISA. For statistical analysis, Wilcoxon, Friedman and Mann-Whitney tests for nonparametric data were applied. The p value was set at < 0.05. Regarding the angulation, the technique presented was effective for both groups, and we had an increase in the verticalization speed of approximately 10% in the group in which there was PBM, over the course of 3 months. Although there was no statistically significant difference regarding pain and tissue inflammation, PBM was able to modulate IL-1β expression in the first 72h. It is concluded that PBM was effective in accelerating the orthodontic movement of molar verticalization and in modulating IL-1β, however it was not able to modulate pain for 3 months.